(untitled) (Jurnal Manajemen dan Organisasi, 2016)
Economic growth is a measure of the national development of the world where banks play an important role in the stability of economic growth. The main function of banks is as a collector and distributor of public funds that aims to increase the standard of living people. Successfully collected funds will be channeled back in the form of credit. Currently, the bank main income is derived from distribution of credit. However, credit is also one of the factors that caused banking collapse when credit problems happened. So, management of funds of third parties becomes an important thing that it is a credit risk from funds distribution. This study aims to (1) Analyze the composition of third party funds (savings, giro, deposito), and (2) Analyze the development of DPK, NPL, and profit. Research conducted in the PT Bank X Tbk. From the research, it was found that the composition of the funds of third parties on PT Bank X is dominated by deposito that has the largest contribution to the total of DPK (56,50%), while savings and giro has contributed almost the same, namely that each of 21,90% and 21,61%. There are fluctuations of DPK, NPL, and profit PT Bank X during the period 1999-2007. DPK PT Bank X was happening in the year 2007 amounting to Rp 247.355.023 (in million) with growth of 20,25% and the lowest occurred in 1999, amounting to Rp 148.005.573 (in millions). The lowest NPL happenned in the year 2004 amounting to 7,10% and the highest occurred in 1999, amounting to 70,84%. PT Bank X has a relatively large loss in 1999, namely Rp 68.155.446 (in millions) and then experienced a rapid development of year 2000 with profit growth of 103%. However, in 2005 had experienced a decline of 84% but it could have been increased again in the years 2006 to 2007 those were 130% and 124% respectively.